Japanese sentence patterns for JLPT N5: training book - Noboru Akuzawa ([Place of publication not identified] : Amazon Digital Services LLC, 2018)
Many Japanese learners face the same challenge: they know vocabulary and grammar rules, but when it comes to speaking, the words don$1 (Bt come out naturally. Without mastering sentence flow, conversations remain difficult and frustrating.s
Keywords: Japanese language; Japanese language Self-instruction